Large Specific Surface Area Macroporous Nanocast LaFe1−xNixO3: A Stable Catalyst for Catalytic Methane Dry Reforming. (21st December 2019) - Chen, Chunfeng; Meng, Zhaojun; Wang, Zijun
Abstract : Macroporous nanocast perovskites, LaFe1− x Ni x O3 ( x  = 0.3, 0.5, and 0.7), were synthesized by using a nanocasting technique with SBA-15 as a template and applied to methane dry reforming (MDR). The prepared catalysts were characterized by X-ray diffraction, transmission electron microscopy, specific-surface-area analysis, hydrogen temperature-programmed reduction, and thermogravimetric analysis. LaFe1− x Ni x O3 revealed a large specific surface area, which could enhance its catalytic activity. The catalysts were reduced to Ni/LaFeO3 -La2 O3 in the MDR reaction. The alkaline additive, La2 O3, and perovskite oxide, LaFeO3, strongly interacted with the active component to reduce the surface energy of metal particles and prevent aggregation of active Ni. The results showed that LaFe0.5 Ni0.5 O3 and LaFe0.3 Ni0.7 O3 perform better than LaFe0.7 Ni0.3 O3 . More importantly, LaFe0.5 Ni0.5 O3 had a very long lifetime (>80 h) in the MDR reaction. The LaFe0.5 Ni0.5 O3 catalyst showed excellent stability in the MDR reaction and has potential use in industrial applications.